Developing and Strengthening Networks to Promote Resilience After Disasters - Angela B. Lindsey; Samantha Goldenberg; Cassie Wandersee (EDIS, 2018)
The HGHC series includes thirteen publications that focus on the work of the community outreach and dissemination team, including community engagement, outreach, and research result dissemination. This 3-page document focuses on developing and strengthening networks before they are challenged to promote resilience in and after a disaster. Written by Angela B. Lindsey, Samantha Goldenberg, and Cassie Wandersee, and published by the UF/IFAS Department of Family, Youth and Community Sciences, April 2018. http://edis.ifas.ufl.edu/fy1477